Impact of climate on pipe failure: predictions of failures for drinking water distribution systems - Wols, B.A.; Thienen, P. van (European Journal of Transport and Infrastructure Research, 2016)
The integrity of drinking water distribution systems (DWDS) may be influenced by climate change. Using the statistical relations between failure frequencies and weather conditions described in our previous work (Wols & Van Thienen 2014a), a methodology is proposed to assess the effect of climate change on future DWDSs. The effect of climate change is combined with the evolution of the DWDS. This analysis can be conducted for any DWDS, for which historical failure registrations and weather parameters are available. The proposed methodology can therefore assist in the construction and maintenance planning of DWDSs. The methodology has been worked out for the Dutch drinking water distribution network. The results show that failures in networks with high AC proportions will increase as a result of expected climate change in the Netherlands, whereas failures in networks with high PVC and GCI proportions will even slightly reduce.